Anatase nanoparticle surface reactivity in NaCl media a CD-MUSIC model interpretation of combined experimental and density functional theory studies - Ridley, Moira K (Langmuir : the ACS journal of surfaces and colloids, 2013)
The effect of particle size on the primary charging behavior of a suite of monodisperse nanometer diameter (4, 20, and 40 nm) anatase samples has been quantitatively examined with macroscopic experimental studies. The experimental results were evaluated using surface complexation modeling, which explicitly incorporated corresponding molecular-scale information from density functional theory (DFT) simulation studies. Potentiometric titrations were completed in NaCl media, at five ionic strengths (from 0.005 to 0.3 m), and over a wide pH range (3-11), at a temperature of 25 °C. From the experimental results, the pH of zero net proton charge (pHznpc) for the 4 and 20 nm diameter samples was 6.42, whereas the pHznpc was 6.22 for the 40 nm sample. The slopes of the net proton charge curves increased with an increase in particle size. Multisite surface complexation and charge distribution (CD) models, with a Basic Stern layer description of the electric double layer, were developed to describe all experimental data. Fits to the experimental data included an inner-sphere Na-bidentate species, an outer-sphere Na-monodentate species, and outer-sphere Cl-monodentate species. DFT simulations found the Na-bidentate species to be the most stable species on the (101) anatase surface (the predominant crystal face). The CD value for the Na-bidentate species was calculated using a bond valence interpretation of the DFT-optimized geometry. The Stern layer capacitance value varied systematically with particle size. The collective experimental and modeling studies show that subtle differences exist in the interface reactivity of nanometer diameter anatase samples. These results should help to further elucidate an understanding of the solid-aqueous solution interface reactivity of nanosized particles